Bionomics and population growth statistics of Cyrtomenus bergi (Hemiptera: Cydnidae) on different host plants - Riis, L; Bellotti, Anthony C.; Arias, B. (Florida Entomological Society, 2005)
Cyrtomenus bergi Froeschner (Hemiptera: Cydnidae) is a polyphagous subterranean burrower bug reported on various crops and weeds in the field. Bionomics and population growth statistics of C. bergi while feeding on peanut (Arachis hypogaea L.), pinto peanut (Arachis pintoi, Krapovickas et Gregory), maize (Zea mays L.), sorghum (Sorghum bicolor [L.] Moench), welsh onion (Allium fistulosum L.),and sweet and bitter cassava (Manihot esculenta Crantz) were calculated from development time, survival of immature stages, and reproduction and female longevity under laboratory conditions. Free-choice host plant selection among peanut, maize and sweet cassava was recorded with separate rearings of C. bergi from the different hosts. Optimal performance ofC. bergi as measured by fecundity, survival, and intrinsic rate of population increase occurred on peanut and pinto peanut followed by maize. Sweet cassava, sorghum, and welsh onion were not favorable hosts, and C. bergi was unable to complete its life cycle on bitter cassava. In the free-choice test, insects reared on peanut and maize prior to the experiments were less active in their search for food, whereas insects reared on cassava prior to the experiment showed a clear preference for peanut and maize over cassava. Our results show that C. bergi is highly polyphagous, however, some host plants are strongly preferred over others. Cassava is not a preferred host and weeds in and around the cassava field may serve as alternative host plants that could maintain populations of C. bergi in cassava.